Digital Parenting: Penguatan Kedekatan Emosional Orang Tua dan Anak Usia Dini di Era Digital - Risna, Inten; Rizka, Siti; Masulah, Masulah; Sukriyah, Sukriyah; Sofiawati, Ratu Efi; Rohmawati, Imah; Annisa, Tiara; Assabila, Salwa (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Digital technology development has significantly influenced parenting patterns, particularly in early childhood. Young children are highly vulnerable to digital exposure as they are in a critical developmental stage. This community service activity was conducted at RA Bina Wanita Bahagia, Serang City, Banten Province, on February 13, 2026, involving 30 parents. The objective was to improve parents’ understanding of digital parenting based on early childhood development and strengthen emotional bonding. Methods included counseling, training, interactive discussions, and evaluation through pre-test and post-test. The results indicate improved parental understanding of developmentally appropriate digital parenting and increased awareness of direct emotional interaction. This activity contributes to promoting healthy and adaptive parenting practices for early childhood in the digital era.